2018
DOI: 10.1080/2162402x.2018.1426517
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma expresses the immunoregulatory ligand CD200 and induces immunosuppressive macrophages and regulatory T cells

Abstract: Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer that responds to PD-1/PD-L1 immune checkpoint inhibitors. CD200 is another checkpoint modulator whose receptor is found on tumor-promoting myeloid cells, including M2 macrophages. We found high mRNA expression in MCC tumors, and CD200 immunostaining was demonstrated on 95.5% of MCC tumors. CD200R-expressing myeloid cells were present in the MCC tumor microenvironment. MCC-associated macrophages had a higher average CD163:CD68 staining ratio (2.67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…CD200R is principally expressed on immune cells of monocyte-macrophage lineage, with an emphasis on myeloid-derived suppressor cells (MDSCs) [ 19 , 24 ]. Additionally, Gaiser et al found evidence of CD200R-expressing macrophages in Merkel cell carcinoma and suggested a role for the induction of an immunosuppressive M2 phenotype [ 25 ]. This is supported, diagonally, by the fact that we detected immune cells staining double positive for both CD200R and PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…CD200R is principally expressed on immune cells of monocyte-macrophage lineage, with an emphasis on myeloid-derived suppressor cells (MDSCs) [ 19 , 24 ]. Additionally, Gaiser et al found evidence of CD200R-expressing macrophages in Merkel cell carcinoma and suggested a role for the induction of an immunosuppressive M2 phenotype [ 25 ]. This is supported, diagonally, by the fact that we detected immune cells staining double positive for both CD200R and PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…In BCCs, recruited Tregs build an immunosuppressive niche by locally synthesizing TGF-β (Omland et al, 2016). In MCC, M2 macrophages and Tregs present in the tumor maintain an immunosuppressive state contributing to a pro-tumorigenic microenvironment (Gaiser et al, 2018). Interestingly, increased recruitment of CD8 + T cells to the skin is associated with better prognosis in MCCs (Touzé et al, 2011).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…Non-melanoma skin cancers such as extramammary Paget’s disease (EMPD), cutaneous squamous cell carcinoma (cSCC) and Merkel cell carcinoma (MCC) also possess heterogeneous CD163 + TAMs that could secrete an array of cytokines and chemokines in lesional skin to regulate the tumor microenvironment [ 1 , 20 , 21 , 22 ]. For example, serum sCD163 is increased in patients with EMPD compared to healthy donors [ 23 ], suggesting that CD163 + TAMs are constitutively activated in the lesional skin of EMPD.…”
Section: Significance Of Immunosuppressive Cells In Developing Skimentioning
confidence: 99%
“…On the other hand, as Petterson et al reported [ 21 ], CD163 + TAMs in cSCC heterogeneously polarized from M1 to M2, suggesting heterogeneous activation states of TAMs. CD163 + TAMs contribute to the tumor microenvironment in MCC to promote tumor development by inducing lymphangiogenesis and immunosuppressive cells such as Tregs [ 22 , 24 ]. These reports suggested that CD163 + TAMs could represent a therapeutic target for the treatment of these non-melanoma skin cancers.…”
Section: Significance Of Immunosuppressive Cells In Developing Skimentioning
confidence: 99%